Beneficial Effects of Nut Consumption on Cognitive Function Among Elderly: Findings From a 6-Year Cohort Study - Li, Fudong; Jiang, Weiping; Wang, Junbiao; Zhang, Tao; Gu, Xue; Zhai, Yujia; Wu, Mengna; Xu, Le; Lin, Junfen (Frontiers in Aging Neuroscience, 2022)
Objective: To evaluate the longitudinal association of nut consumption with cognitive function in Chinese elderly. Methods: We analyzed the data from Zhejiang Ageing and Health Cohort Study including 9028 participants. Nut consumption was evaluated in baseline questionnaire beginning at 2014. Cognitive function was assessed repeatedly through the Mini-Mental State Examination (MMSE) at baseline and three waves of follow-up (2015, 2016, and 2019-2020). Cognitive impairment was defined using education-specific cut-off points. Log-binomial regression models with the Generalized Estimating Equations, controlled for an extensive range of potential confounders, were utilized to evaluate the association and estimate relative risk (RR). Results: After 6 years of follow-up, 3266 (36.18%) participants were indicated as cognitive impairment by MMSE at least once. Compared with non-consumers or less-than-weekly consumers, participants consuming ≥70 g/week of nuts had 17% lower risks of cognitive impairment (RR=0.83, 95% CI 0.75-0.91), whereas no association was found in those consuming <70 g/week of nuts. Moreover, relatively infrequent higher-amount consuming (≥ 70g within one consuming day each week) was not associated with better cognitive performance. Furthermore, we did not observe significant effect modification caused by frequency of other food intake. Conclusion: Higher nut consumption was prospectively related to a lower risk of cognitive impairment in Chinese elderly.